Narrativas de professores de geografia: histórias de vida e trajetórias formativo-profissionais na composição da identidade docente - Silva, Maria José Sousa da (2022)
The research proposed here has the objective of analyzing the process of constitution of the identity of the Geography teachers in basic education, according to the life stories, and the formative-professional trajectories. Therefore, it was based on a qualitative approach, anchored in the method (auto). The search for understanding the subjectivity of subjects based on the understanding they have about their own formative-professional trajectories was fundamental from the analysis and interpretation of oral and written narratives as research devices. The data presented are the result of training memorials, narrative interviews and questionnaires. The exposed narratives allowed the understanding of the way in which the collaborating professors see their initial and practical training, relating life stories to the training-professional processes experienced by these professionals. Data analysis was based on discourse analysis, in the hope of promoting an understanding of how professors who collaborated in the research conceive and describe their own formative processes. The narratives express the way that the teachers see their profession, how they arrived at the choice of a degree in Geography and the way that these teachers see “being a teacher” from the very identity they constituted throughout their formative-professional trajectories and the way how they mobilize the knowledge necessary for their practice. This research showed that the constitution of the teaching identity brings together elements from different life contexts and that this process is continuous in the teacher's life. This research also made it possible for the collaborators to reflect on the importance of their stories as formative elements and contributions to the formation of other subjects who will be able to read and interpret their narratives. In this sense, I hope that this work becomes a device for future research, reading and training for teachers, researchers, students and readers who are interested in understanding the formative process of the Geography teacher, in (auto)biographical narratives and that can serve inspiration for other researchers to deepen the themes and questions raised here.